CLASSIFICATION CRITERIA USED AS BASIS FOR AN EFFECTIVE MUNICIPAL PROPERTY MANAGEMENT - Daniela Constantin; Mariana Dragusin; Marius Profiroiu; Constantin Mitrut; Alina Iosif-Balalia; Raluca Petrescu (European Regional Science Association (ERSA), 2011)
The immediate reality reveals a significant difference in terms of practical use between public and private property management. It can be noticed that the emphasis is placed to a higher extent on the private property management, which is more profit-oriented, compared to the public property management, driven by the public sector's purpose to achieve the welfare of its citizens. However, during the last years, the interest in assets management has grown also at municipal level. The motivation for applying a strategic municipal property management comes from the necessity to mach the municipal long-term needs for their own use of properties, as well as to use their properties in order to attract investment and promote sustainable socio-economic development of their cities and regions. Referring to the Balkan area, a lack of strategy can be noticed with regard to the real asset management of municipal properties. In order to support the efforts of the municipalities in articulating real asset strategies, a project on "Municipal Property Management in South- Eastern Cities (PROMISE)" is carried on (2009-2012), supported by the ERDF within the South-East Territorial Co-operation Programme. It is expected to contribute to supporting urban environmental sustainability improvement through regeneration programmes, to promoting economic sustainability via the encouragement of innovative investments, to facilitating social sustainability through urban social infrastructure development, as well as to improving social services and social cohesion policies. This paper, derived from the above mentioned project, emphasizes the importance of using the most suitable classification criteria in order to ensure an effective municipal property management. In the beginning a comprehensive international literature review and a structured conceptual clarification are provided, referring to papers like those by Jolicoeur and Barret (2004) and Musil (2006) as having had an important contribution to this topic. Then, specific classification criteria in the case of Romania are pointed out, followed by a discussion on features of assessment extracted from the evaluation practice. The results may contribute to the identification of reliable variables that can be used as a starting point for the strategic management of municipal properties.
Keywords: 330; municipal property; criteria; strategic management